From Offline to Online: Understanding Chinese Single Mothers’ Uncertainty Management in Interpersonal and Online Contexts - Kuang, Kai; Zhao, Xiaoman; Basnyat, Iccha; He, Tianping (Frontiers in Psychology, 2022)
Divorced and unwed single motherhood is heavily stigmatized in Chinese cultural context, preventing Chinese single mothers from actively seeking the information and support needed and negatively impacting their wellbeing. Drawing on the theory of motivated information management (TMIM), this study tested how perceived stigma and cultural norms influenced Chinese single mothers’ search for information and social support from families, friends as well as from online communities. Using two-wave data collected from 226 single mothers, findings support the utility of the TMIM in explaining information management and support seeking behaviors and contribute to situating the TMIM process within larger socio-cultural contexts. Practical implications regarding how to facilitate more effective uncertainty management and enhance Chinese single mothers’ wellbeing in interpersonal vs. online contexts are discussed.